2021
DOI: 10.21037/jgo-20-350
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of modified bevacizumab-XELOX therapy in Japanese patients with stage IV recurrent or non-resectable colorectal cancer

Abstract: Background: Neoadjuvant chemotherapy (NAC) has been conducted for patients with non-resectable colorectal cancer; however, few reports of a systematic approach to NAC exist. At our hospital, bevacizumab with capecitabine and oxaliplatin (B-mab XELOX) has been used as chemotherapy for Stage IV colorectal cancer since 2014. We aimed to evaluate the efficacy and safety of NAC with a molecular-targeting agent for Stage IV colorectal cancer.Methods: A retrospective, single-institute analysis was performed including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, we did not consider mutations in RAS and BRAF [ 27 ]. Our treatment strategy positioned radiation therapy as an optional treatment in case of postoperative local relapse [ 29 ]. However, a recently published Japanese clinical guideline recommends deciding on the chemotherapy regimen after performing molecular testing and determining the tumor mutational burden (TMB) and microsatellite instability (MSI) status [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we did not consider mutations in RAS and BRAF [ 27 ]. Our treatment strategy positioned radiation therapy as an optional treatment in case of postoperative local relapse [ 29 ]. However, a recently published Japanese clinical guideline recommends deciding on the chemotherapy regimen after performing molecular testing and determining the tumor mutational burden (TMB) and microsatellite instability (MSI) status [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a clinical study involving 70 patients with colorectal cancer, it was revealed that the addition of bevacizumab to the NAC produced a good objective response rate, clinical benefit rate, R0 resection rate, and acceptable incidence of adverse reactions. It was indicated that NAC plus bevacizumab is a safe and effective treatment strategy that can improve the life quality of patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 41 patients collectively received 299 chemotherapy courses. The median number of courses was 6.0 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], corresponding to about 6 months of treatment, and sufficient dose intensity could be obtained (31,32). In about 50% of patients, the duration of a treatment cycle was 5 and not 4 weeks because the off period was 3 rather than 2 weeks (data not shown).…”
Section: Efficacymentioning
confidence: 99%
“…Accordingly, the treatment regimens FOLFOX4 and FOLFOX6 have frequently been studied in Japanese people because of their smaller body frame ( 18 , 19 ). As we have previously reported, when determining the dose, we aimed to use a minimal chemotherapy dose ( 20 , 21 ). Therefore, at our hospital, we frequently use B-mab-CAPOX (Cape + L-OHP) as the first-line therapy for stage IV recurrent or nonresectable colorectal cancer, and we have reported on the efficacy and safety of this approach ( 20 , 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation